Decolorization of Orange II by Mixed Culture of Enterococcus faecalis ID6017 and Chryseobacterium indologenes ID6016 - VINCENTIA IRENE MEITINIARTI; KRIS HERAWAN TIMOTIUS; ENDANG SUTARININGSIH SOETARTO; EKO SUGIHARTO (Indonesian Society for microbiology, 2012)
Previous work showed that Enterococcus faecalis ID6017 and Chryseobacterium indologenes ID6016 were able to decolorize the orange II qualitatively. In that experiment, E. faecalis could decolorize orange II more rapidly than C. indologenes. The objective of this study was to examine the decolorization of orange II by mixed culture and the growth of both bacterial species on orange II containing medium. The experiment was done in 500 mL sterilized Erlenmeyer flasks containing 285 mL growth media with 80 mg L-1 orange II. Five different treatments were performed in this project, i.e. medium was inoculated with (i) 15 mL of sterile aquadest, (ii) 15 mL of C. indologenes, (iii) 15 mL of E. faecalis, (iv) 7.5 mL of C. indologenes and 7.5 mL of E. faecalis, and (v) 7.5 mL of E. faecalis until decolorization occured , followed by inoculation with 7.5 mL of C. indologenes. Bacterial growth (total cells number), orange II, glucose, and suphanilic acid, as intermediate product of orange II decolorization, concentrations were measured every 2 h.The maximum decolorization of orange II was observed in the medium inoculated with a mixed culture of E. faecalis and C. indologenes. Decolorization of orange II occurred of growth and gave final concentration of sulphanilic acid of 7.06 mg L-1. During culture both species grow in equilibrium in terms of population.